Factors affecting decreased physical activity during the COVID-19 pandemic: an age-, gender-, and body mass index-matched study - Shin, Jhin-Yi; Lee, Jaemoo; Lee, Jung-Min; Ho, Nam Yoon (Frontiers in Public Health, 2023)
Purpose This study aims to investigate the association between factors affecting decreased physical activity (PA) during the COVID-19 pandemic by matching groups based on age, gender, and BMI variables using public Community Health Survey (CHS) data. Methods Data from the CHS was selected and used to investigate health-related factors related to PA, including demographic, psychological, behavioral characteristics, sociocultural, and chronic disease. Exact group matching was conducted based on age, gender, and BMI variables. Frequency analysis, Chi-square test (χ2 test), and multinominal logistic regression analysis were performed to analyze the data, and odds ratio (OR) and 95% confidence interval (95% CI) were presented. The study also examined the impact of COVID-19 on PA, the fear of PA infection. Results The logistic regression analysis by gender showed that PA decreased in all age groups, males, and females during the COVID-19 pandemic. The decrease in PA was lower in age groups other than those aged 60 or older. Stress experience, residence area, housing type, drinking, smoking, education level, and fear of infection were found to affect decreased PA due to COVID-19. Specifically, experiencing stress (Odds Ratio [OR] = 1.178; 95% Confidence Interval [CI] = 1.054 ~ 1.317) and increased smoking (OR = 1.332; 95% CI = 1.073 ~ 1.653) had a slightly higher impact on decreased PA. Conversely, living in a suburban area (OR = 0.653; CI = 0.585 ~ 0.728), having public housing (OR = 0.836; CI = 0.754 ~ 0.928), having less than a high school education (OR = 0.813; CI = 0.729 ~ 0.907), staying the same with alcohol (OR = 0.567; CI = 0.507 ~ 0.633) and smoking (OR = 0.836; CI = 0.728 ~ 0.959), and having low fear of infection (OR = 0.817; CI = 0.737 ~ 0.905) had a slightly lower impact on decreased PA. Conclusion PA should be maintained or increased, particularly in the context of social distancing measures during the pandemic. To ensure that PA can be sustained, a program should be developed that considers the individual’s geographical location, economic status, lifestyle, and environment.